A Systematic Review of the Tumor-Infiltrating CD8+ T-Cells/PD-L1 Axis in High-Grade Glial Tumors: Toward Personalized Immuno-Oncology - Shadbad, Mahdi Abdoli; Asadzadeh, Zahra; Hosseinkhani, Negar; Derakhshani, Afshin; Alizadeh, Nazila; Brunetti, Oronzo; Silvestris, Nicola; Baradaran, Behzad (Frontiers in Immunology, 2021)
Based on preclinical findings, programmed death-ligand 1 (PD-L1) can substantially attenuate CD8+ T-cell-mediated anti-tumoral immune responses. However, clinical studies have reported controversial results regarding the significance of the tumor-infiltrating CD8+ T cells/PD-L1 axis on the clinical picture and the response rate of patients with high-grade glial tumors to anti-cancer therapies. Herein, we conducted a systematic review according to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines to clarify the clinical significance of the CD8+ T cells/PD-L1 axis and elucidate the impact of this axis on the response rate of affected patients to anti-cancer therapies. Indeed, a better understanding of the impact of this axis on the response rate of affected patients to anti-cancer therapies can provide valuable insights to address the futile response rate of immune checkpoint inhibitors in patients with high-grade glial tumors. For this purpose, we systematically searched Scopus, Web of Science, Embase, and PubMed to obtain peer-reviewed studies published before 1 January 2021. We have observed that PD-L1 overexpression can be associated with the inferior prognosis of glioblastoma patients who have not received chemo-radiotherapy before. Besides, exposure to anti-cancer therapies, e.g., chemo-radiotherapy, can up-regulate inhibitory immune checkpoint molecules in tumor-infiltrating CD8+ T-cells. Unlike unexposed glioblastoma tissues, increased tumor-infiltrating CD8+ T-cells in anti-cancer therapy-exposed tumoral tissues can be associated with the inferior prognosis of affected patients. Besides identifying new inhibitory immune checkpoints, single-cell sequencing technologies can provide valuable insights into the expression profile of inhibitory immune checkpoints in the tumor micromovement, and administrating immune checkpoint inhibitors based on the data from single-cell sequencing technologies can increase patients' response rates, decrease the risk of immune-related adverse events development, prevent the immune-resistance development, and reduce the risk of tumor recurrence.